2009
DOI: 10.1016/j.sjbs.2009.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chlorpyrifos on healing of cutaneous leishmaniasis lesions after treatment with Pentostam®

Abstract: The insecticide chlorpyrifos (CPF) is widely used in the Kingdom of Saudi Arabia (KSA) to control agricultural pests. The present work is a preliminary investigation of the effect of CPF on healing of cutaneous leishmaniasis (CL) lesions, caused by Leishmania major in farmers exposed to this insecticide, after treatment with Pentostam(®). Lesion diameters were measured and CPF concentrations in the blood plasma of farmer and non-farmer CL patients in Al-Ahsa were detected by gas chromatography/mass spectrometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…We suggest that the elimination of parasites is reduced because MΦ are subsequently reprogrammed to switch to the immunosuppressive/tissue-repairing phenotype of M2 cells (mainly M2a and M2d), which contributes to uncontrolled parasite replication. These results are consistent with those observed in some human populations 17 , where chronic exposure to low levels of the OP pesticide chlorpyrifos exacerbated infection with Leishmania sp . and delayed the healing of cutaneous leishmaniasis lesions due to alterations in the immune response.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We suggest that the elimination of parasites is reduced because MΦ are subsequently reprogrammed to switch to the immunosuppressive/tissue-repairing phenotype of M2 cells (mainly M2a and M2d), which contributes to uncontrolled parasite replication. These results are consistent with those observed in some human populations 17 , where chronic exposure to low levels of the OP pesticide chlorpyrifos exacerbated infection with Leishmania sp . and delayed the healing of cutaneous leishmaniasis lesions due to alterations in the immune response.…”
Section: Discussionsupporting
confidence: 92%
“…Some epidemiological studies report that exposure to OP pesticides may increase the rate and risk of infections in rural populations 16 , exacerbating cutaneous leishmaniasis and inducing a low response to treatment in farmers exposed to chlorpyrifos, an OP pesticide that generates DETP and DEP 17 . In vivo studies showed that these effects on the immune response may be due to a decrease in the levels of plasma nitric oxide (NO) and interferon (IFN)-γ and to the increase in the activity of arginase, which explains the inability of macrophages (MΦ) to control the parasites or induce an adequate immune response against them 18 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been revealed that induction of arginase enzyme favored the replication of leishmania inside the macrophages, but inhibition of arginase reduces the number of parasites found in macrophages [15]. Furthermore, Al-Dawood et al, 2009 [12] reported that leishmaniasis persons exposed to CPF exhibited a delay in the healing of their skin lesions as compared to leishmaniasis persons not exposed to CPF. Therefore, high level of arginase activity as a result of CPF exposure associated with adding curcumin directly on the insect bites may explain the delayed healing of skin lesions in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Arginase activity is induced by cytokines secreted by T helper-2 lymphocyte, while iNOS is activated by gamma interferon (IFN-gamma) secreted by T helper-1 lymphocyte [7]. Recent studies reported that chronic exposure to low levels of the pesticide aggravates and delays the healing of cutaneous leishmaniasis lesions [12]. In Tabouk region, North of KSA, farmers are inevitably exposed to high amount of chlorpyrifos (CPF) insecticide.…”
Section: Open    Accessmentioning
confidence: 99%